2017
DOI: 10.1093/glycob/cwx034
|View full text |Cite
|
Sign up to set email alerts
|

Biological functions of fucose in mammals

Abstract: Fucose is a 6-deoxy hexose in the l-configuration found in a large variety of different organisms. In mammals, fucose is incorporated into N-glycans, O-glycans and glycolipids by 13 fucosyltransferases, all of which utilize the nucleotide-charged form, GDP-fucose, to modify targets. Three of the fucosyltransferases, FUT8, FUT12/POFUT1 and FUT13/POFUT2, are essential for proper development in mice. Fucose modifications have also been implicated in many other biological functions including immunity and cancer. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
359
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 333 publications
(370 citation statements)
references
References 264 publications
10
359
1
Order By: Relevance
“…[1] Reflecting the important roles of this carbohydrate motif, there are specific enzymes, termed a-l-fucosidases( which are part of al arger class of enzymes termedg lycoside hydrolases [2] ), that act to cleave a-l-fucose moieties from glycoconjugates. Enzymes hydrolyzing fucose from glycoconjugates, a-l-fucosidases, are important targets for inhibitor and probe development.H ere we describe the synthesis and evaluation of novel a-l-fucosidase inhibitors, with X-ray crystallographic analysisu sing an a-l-fucosidase from Bacteroides thetaiotamicron helping to lay af oundation for future developmento fi nhibitors for this important enzymec lass.…”
mentioning
confidence: 99%
“…[1] Reflecting the important roles of this carbohydrate motif, there are specific enzymes, termed a-l-fucosidases( which are part of al arger class of enzymes termedg lycoside hydrolases [2] ), that act to cleave a-l-fucose moieties from glycoconjugates. Enzymes hydrolyzing fucose from glycoconjugates, a-l-fucosidases, are important targets for inhibitor and probe development.H ere we describe the synthesis and evaluation of novel a-l-fucosidase inhibitors, with X-ray crystallographic analysisu sing an a-l-fucosidase from Bacteroides thetaiotamicron helping to lay af oundation for future developmento fi nhibitors for this important enzymec lass.…”
mentioning
confidence: 99%
“…Terminal fucosylation is a common modification found on many N -glycans, mucin O -GalNAc glycans, and glycolipids (36). At least ten fucosyltransferases ( FUT1–7 and FUT9–11 ) can function to add terminal fucose to oligosaccharide chains on these molecules leading to diverse biological functions and as well as is considerable redundancy (37). Studies in mice have shown that Fut4 and Fut7 are functionally redundant, and the much weaker contribution of Fut4 to fucosylation of selectin ligands to form sLe x was only revealed in the context of Fut7 deficiency (13).…”
Section: Discussionmentioning
confidence: 99%
“…[1] This posttranslational modification regulates many biological processes such as cell adhesion or innate immunity.I ti sa ssociated with pathologies like cancers,w here altered glycosylation is ah allmark. [1] This posttranslational modification regulates many biological processes such as cell adhesion or innate immunity.I ti sa ssociated with pathologies like cancers,w here altered glycosylation is ah allmark.…”
mentioning
confidence: 99%
“…[1] This posttranslational modification regulates many biological processes such as cell adhesion or innate immunity.I ti sa ssociated with pathologies like cancers,w here altered glycosylation is ah allmark. [3] Several core-fucosylated glycoproteins,s uch as alpha-fetoprotein (AFP-L3), [1,2] prostate-specific antigen (PSA), [4] or haptoglobin [5] are used as serological biomarkers for the detection of hepatocellular carcinoma, prostate,a nd pancreatic cancers, respectively.Core fucosylation strongly affects the bioactivity of therapeutical N-glycoproteins.Its presence in the Fc region of monoclonal antibodies (mABs) impairs their recognition by FcgRIIIA receptors and thus,l owers their efficacy in antibody-dependent cellular cytotoxicity (ADCC). [3] Several core-fucosylated glycoproteins,s uch as alpha-fetoprotein (AFP-L3), [1,2] prostate-specific antigen (PSA), [4] or haptoglobin [5] are used as serological biomarkers for the detection of hepatocellular carcinoma, prostate,a nd pancreatic cancers, respectively.Core fucosylation strongly affects the bioactivity of therapeutical N-glycoproteins.Its presence in the Fc region of monoclonal antibodies (mABs) impairs their recognition by FcgRIIIA receptors and thus,l owers their efficacy in antibody-dependent cellular cytotoxicity (ADCC).…”
mentioning
confidence: 99%
See 1 more Smart Citation